2021
DOI: 10.21037/atm-21-3734
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis and treatment of breast cancer with brain metastases and establishment of a prognostic model: a 10-year, single-center, real-world study of 559 cases

Abstract: Background: This study involved a retrospective analysis of 559 metastatic breast cancer (MBC) patients with brain metastasis (BM). We aimed to establish the effectiveness of different preferred treatment methods and factors affecting overall survival following BM diagnosis (BMOS) and explore the feasibility of systemic treatment for MBC patients with BM.Methods: Univariate and multivariate analyses were used to assess the efficacy of different preferred treatments and other factors associated with BMOS, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…This accounted for a mere 0.63% of the overall breast cancer cases observed during the same period. [ 2 ] These findings align with previously published incidence rates. [ 3 ] It was found that the age of MBC onset ranged between 34 years and 70 years, with a median of 56 years, while the age of recurrence ranged from 42 years to 72 years (median: 59.5 years).…”
supporting
confidence: 91%
“…This accounted for a mere 0.63% of the overall breast cancer cases observed during the same period. [ 2 ] These findings align with previously published incidence rates. [ 3 ] It was found that the age of MBC onset ranged between 34 years and 70 years, with a median of 56 years, while the age of recurrence ranged from 42 years to 72 years (median: 59.5 years).…”
supporting
confidence: 91%
“…We believe what the authors stated was a mistake after reviewing the original findings in the Supplementary material, which indicated that the risk of all-cause death rose with age (increased by per 1, HR = 1.02, 95% CI 1.01-1.03, p < 0.001). Another study found that in a univariable Cox model, age did not correlate with breast cancer BMs survival time (22). A possible explanation for this might be the potentially inappropriate classification of age groups.…”
Section: Comparison With Other Studiesmentioning
confidence: 97%
“…Studies have shown that increasing age has generally been associated with poorer survival of BMs (12)(13)(14). There were, however, some inconsistent results (11,22). Furthermore, there is no credible data on the impact of age on the prognosis of breast cancer patients with BMs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in a cohort of 168 patients, retrospective studies found that surgery or radiotherapy combined with pyrotinib therapy significantly improved overall survival (OS) in patients with HER2+ MBC [ 31 ], and it may have advantages in preventing brain metastasis, as well as good efficacy in patients with brain metastasis. For MBC patients with brain metastasis, systemic drug therapy is beneficial because it effectively delays local intracranial therapy [ 32 ]. At the genetic level, an RWS showed that FGFR, TP53 and FLT1 genetic aberrations, as well as positive HER2, can increase the risk of brain metastasis in MBC patients, and FGFR genetic aberration alone predicted poor prognosis [ 33 ].…”
Section: Breast Cancer (Bc)mentioning
confidence: 99%